2020
DOI: 10.1002/esp.4970
|View full text |Cite
|
Sign up to set email alerts
|

Erosion, transport and deposition of a sediment replenishment under flood conditions

Abstract: River reaches downstream of dams with constant residual discharge often lack sediment supply and periodic high flows due to dam sediment retention and flow regulation, respectively. To test a novel multi-deposit methodology for defining environmental flows for activating the dynamics of the river morphology downstream of dams, a flood was released from Rossens Dam in Switzerland. This event was combined for the first time with a multi-deposit configuration of sediment replenishment consisting of four artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…For our currently performed trials, we report a 100% detection rate of tracked objects, even though they were transported in the bottom of the river flow channel and immersed at depths estimated to be up to 1 m during some of the monitored floods. This detection rate is higher than the detection rate obtained so far with RFID station using PIT tags, ranging from 16% to 39% [12,14]. This detection rate is defined as the number of tracked objects that were located upstream of the e-RFIDuino station once it was installed and that were detected before e-RFIDuino station removal divided by the number of tracked objects that were located upstream of the e-RFIDuino station once it was installed and that were recovered downstream of the e-RFIDuino station by pedestrian operators or UAV survey.…”
Section: Validation and Characterizationmentioning
confidence: 58%
See 1 more Smart Citation
“…For our currently performed trials, we report a 100% detection rate of tracked objects, even though they were transported in the bottom of the river flow channel and immersed at depths estimated to be up to 1 m during some of the monitored floods. This detection rate is higher than the detection rate obtained so far with RFID station using PIT tags, ranging from 16% to 39% [12,14]. This detection rate is defined as the number of tracked objects that were located upstream of the e-RFIDuino station once it was installed and that were detected before e-RFIDuino station removal divided by the number of tracked objects that were located upstream of the e-RFIDuino station once it was installed and that were recovered downstream of the e-RFIDuino station by pedestrian operators or UAV survey.…”
Section: Validation and Characterizationmentioning
confidence: 58%
“…The Slender III antenna, which has a semi-directional sensing field, was fixed on the right bank with an angle of approximatively 45°between the antenna nadir and the vertical axis, and with an angle of 45°b etween the antenna plan and the river channel axis. In that location, about 3 m above the channel bottom, the e-RFIDuino station cannot be damaged by river flow like it has been previously experimented [13,14].…”
Section: Validation and Characterizationmentioning
confidence: 97%
“…The ecomorphological state of the Sarine River in Switzerland, which can be adequately represented by, e.g., the hydro-morphological index of diversity (HMID) [41], was reported to benefit from an SAM that was the first of its kind to be implemented near a reach downstream of the river's residual flow section [42,43]. At the Drôme River in France, investigations on basin-scale environmental changes suggested that sediment augmentation caused by floodplain deforestation can potentially still negatively impact the ecological value of the river network, even while morphological diversity increases [44].…”
Section: Representative Data Surveymentioning
confidence: 99%
“…For example, in residual flow reaches that are downstream of large dams, new riffle structures can be created to free the benthic zone from the nuisance caused by attached algae that travel from the reservoir [20]. Furthermore, the hydro-morphological diversity can be increased [42,43]. Another theoretical benefit of sediment augmentation for the riverbed structure is the deconsolidation and mobilization of the top layer [60] and thus the reduction of clogging of the interstitial pore space.…”
Section: Riverbed Structurementioning
confidence: 99%
See 1 more Smart Citation